Peningkatan Gain dengan Teknik Multilayer Parasitic pada Perancangan Antena Mikrostrip Persegi Panjang 2,4 GHz - Utami, Eva Yovita Dwi; Prabelia, Chorintan; Setiaji, Fransiscus Dalu; Wahyu, Yuyu (Faculty of Engineering, Universitas Tanjungpura, 2019)
Microstrip patch antennas offer low profile and low cost fabrication advantages but limited gain and bandwidth. Some methods and techniques have been proposed and developed to improve gain of microstrip antenna, and one of them is multilayer parasitic technique. In this paper, the design and realization of rectangular patch microstrip antenna with multilayer parasitic for enhancing antenna gain that operates at frequency of 2.4 GHz is presented. The designed antenna consists of one rectangular patch as the main antenna on the first layer and the 2x2 configuration of rectangular patches on the second and third layers as the parasitic substrate. The simulation results show that the single element antenna has a gain of 3.224 dB and increases to 8.593 dB by using the parasitic multilayer antenna. The antenna design was then fabricated using an Epoxy FR4 substrate with a dielectric constant of 4.65 and a thickness of 1.6 mm. The fabricated multilayer parasitic microstrip antenna has dimension of 80 mm x 90 mm x 34.8 mm. The measurement results show that the VSWR value is 1,284 and the return loss is -18,091 dB at the center frequency of 2,442 GHz. The gain of the multilayer parasitic microstrip antenna measurement is 9.1 dB. The operation frequency range is 2.32 - 2.565 GHz at VSWR Â < 2, the bandwidth of 245 MHz is achieved and unidirectional radiation patterns are obtained.